Giuseppe Oddo: chimico “rivoluzionario” e “irriverente” - Noto , Renato (Chimica nella Scuola, 2022)
Giuseppe Oddo can be considered a “revolutionary” and “irreverent” chemist. He was considered “revolutionary” by the reason of he proposed radically innovative positions in relation to traditional ones as well as “irreverent” because of his cultural independence and irritable character also led him to collide with many influential colleagues over the years. The feature that distinguished Oddo’s entire activity was his cultural independence, his ability to break out of pre-packaged schemes that were not his own and to put forward innovative proposals and suggestive hypotheses. Oddo’s scientific output includes, among other things, the first bicyclic structure of camphor, the possibility that the hydrogen atom shared its valence with two other atoms (mesohydria) and, the hypothesis that noble gases such as Krypton and Xenon were not inert.